Antimicrobial activity and mechanisms of multiple antimicrobial peptides isolated from rockfish Sebastiscus marmoratus. Issue 93 (October 2019) - Bo, Jun; Yang, Ying; Zheng, Ronghui; Fang, Chao; Jiang, Yulu; Liu, Jie; Chen, Mengyun; Hong, Fukun; Bailey, Christyn; Segner, Helmut; Wang, Kejian
Abstract: Pathogenic disease is a major factor affecting the aquaculture of the rockfish Sebastiscus marmoratus, an important commercial species inhabiting the nearshore waters of the Western Pacific Ocean . Antimicrobial peptides (AMPs), as critical components of innate immunity, have been considered as promising antibiotic substitutes. The aims of this study were 1) to identify major AMPs in the rockfish, 2) to assess their antimicrobial activity and 3) to evaluate their potential therapeutic application. Six AMPs were identified, Hepcidin 1, liver-expressed antimicrobial peptide 2 (LEAP-2), Piscidin, Moronecidin, NK-lysin and β-defensin through analysis of the liver transcriptome of S. marmoratus . The transcriptional expression profiles of these AMPs were investigated by real-time quantitative PCR (RT-qPCR). These AMPs showed tissue-specific distribution patterns, and S. marmoratus displays a time-, dose- and tissue-dependent expression of AMPs in response to lipopolysaccharide (LPS) challenge. While the synthetic peptides of LEAP-2 and Moronecidin exerted broad-spectrum antimicrobial activity against important aquatic pathogens in vitro by directly disrupting microbial membrane, and no cytotoxicity against murine hepatic cells was observed at the effective concentrations from 5 μM to 40 μM. The existence of multiple AMPs and their distinct tissue distribution patterns and inducible expression patterns suggests a sophisticated, highly redundant, and multilevel network of antimicrobial defensive mechanisms of S. marmoratus . Therefore, S. marmoratus -derived AMPs appear to be potential therapeutic applications against pathogen infections in aquaculture. Highlights: Six AMPs from the liver of S. marmoratus were identified. The AMPs showed distinctly temporal expression patterns upon LPS challenge. LEAP-2 and Moronecidin showed potent broad-spectrum antimicrobial activity. LEAP-2 and Moronecidin acted through disrupting the microbial membrane to execute the antimicrobial function.